Level of Proficiency and Professional Development Needs in Peripheral Online Teaching Roles - González-Sanmamed, Mercedes; Muñoz-Carril, Pablo-César; Sangra, Albert (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
Teaching in virtual environments demands mastery of several teaching competencies. Although the most accepted ones are pedagogical, in order to successfully teach online it becomes necessary to acquire and develop some other competencies, sometimes referred to as peripheral roles (Denis et al., 2004). The aim of this study is to analyse perceptions on the level of proficiency that online teachers have regarding these peripheral roles (social, evaluator, manager, technologist, advisor/counsellor, personal, and researcher), and their professional development needs required to improve their online teaching competencies. A questionnaire was specifically created and validated by experts, and data was gathered from 166 university teachers. The findings show that teachers highlight the importance of the peripheral roles for quality teaching, and thus, professional development programmes should be based on a balance between central and peripheral roles to better train online teachers and increase the quality of their teaching.